Longitudinal Associations of Physical Fitness and Body Mass Index with Academic Performance - Garcia-Hermoso, A (Blackwell Munksgaard, 2021)
No studies have analyzed the longitudinal associations of change in physical fitness components and obesity with academic performance. The aim of the study was to examine longitudinal associations of changes in physical fitness components and body mass index with academic performance among youth, and whether the physical fitness components are moderators of the longitudinal association between obesity and academic performance in youth. Longitudinal analyses (2 years) included 1802 youths. Physical fitness components were assessed following the ALPHA health-related fitness test battery. Academic performance was assessed via school records. Youth in the persistently high cardiorespiratory fitness and motor ability categories (ie, fit at baseline and at 2-year follow-up) had higher academic performance at follow-up than those in the persistently low category. Further, youth with normal weight at baseline and overweight/obesity at follow-up had lower academic performance scores at follow-up compared to those with normal weight. Also, cardiorespiratory fitness may ameliorate the negative influence of excess body mass index on academic performance at follow-up. Promoting physical activity programs at school that include both aerobic exercise and motor tasks to improve physical fitness and reduce body mass index may not only improve physical health, but also contribute toward successful academic development. © 2020 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd